Sex-dependent Lupus Blautia (Ruminococcus) gnavus strain induction of zonulin-mediated intestinal permeability and autoimmunity - Silverman, Gregg J.; Deng, Jing; Azzouz, Doua F. (Frontiers in Immunology, 2022)
Imbalances in the gut microbiome are suspected contributors to the pathogenesis of Systemic Lupus Erythematosus, and our studies and others have documented that patients with active Lupus nephritis have expansions of the obligate anaerobe, Ruminococcus blautia gnavus (RG). To investigate whether the RG strains in Lupus patients have in vivo pathogenic properties, we colonized C57BL/6 mice with individual RG strains from healthy adults or those from Lupus patients. These strains were similar in their capacity for murine intestinal colonization of antibiotic-preconditioned specific-pathogen-free, as well as of germ-free adults, and of their neonatally colonized litters. Lupus-derived RG strains induced high levels of intestinal permeability that was significantly greater in female than male mice, whereas the RG species-type strain from a healthy donor had little or no effects. These Lupus RG strain-induced functional alterations were associated with raised serum levels of zonulin, a regulator of tight junction formation between cells that form the gut barrier. Notably, the level of Lupus RG-induced intestinal permeability was significantly correlated with levels of serum IgG antibodies to the RG cell-wall lipoglycan, and with anti-native DNA autoantibodies that are a biomarker for SLE. Strikingly, gut permeability was completely reversed by oral treatment with larazotide acetate, an octapeptide that is a specific molecular antagonist of zonulin. Taken together, these studies document a pathway by which RG strains from Lupus patients induce a leaky gut and autoimmunity implicated in the pathogenesis of Lupus clinical flares. This is the first demonstration that gut colonization with specific pathobiont strains, from patients with active disease, transmits key features of the clinical autoimmune disease.